Enhancing domain modelling with easy to understand business rules - Christian Bacherler; Christian Facchi; Hans-Michael Windisch (Hochschule Ingolstadt - University of Applied Sciences, 2010)
The model driven software development (MDSD) paradigm is gaining momentum in developing extensive business software applications. With MDSD it can be carried out a significant contribution towards the key factors of success which are flexibility and adherence to delivery dates as well as efficient maintenance and adaptability. With AtomsPro that is introduced here we consequently integrate aspects of domain modelling and software architecture as well as clear and understandable means to enable domain experts to take an active role in the software development process. The challenging aim is to increase the overall ratio of code generated in the development process of enterprise applications by at the same time preserving abilities for efficient maintenance. Hence, we have chosen a fruitful cooperation with several involved project partners.
urn:nbn:de:bvb:573-352
Keywords: 650